1995
DOI: 10.1021/jf00049a030
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects and Survival of Trypsin Inhibitors and the Agglutinin from Soybean in the Small Intestine of the Rat

Abstract: The survival in the rat small intestine of soybean agglutinin or Kunitz or Bowman-Birk trypsin inhibitors was studied by SDS-and native polyacrylamide gel electrophoresis, transblotting, trypsin inhibitor activity assays, and immunochemical determinations. As the inhibitors were bound in enzyme complexes in the small intestine, functional assays were unsuitable. However, as free and bound inhibitors reacted similarly with their antibodies, survival could be assayed by immunoblotting and ELISA. In addition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 12 publications
6
46
0
2
Order By: Relevance
“…8 Intestinal trypsins in the middle and lower segments were more severely suppressed when winged bean TI was fed, suggesting higher survival of the trypsin±TI complex in the intestine. Although this study determined only functional activities but not resistance to intestinal proteolysis, Iwami et al 20 and Hajos et al 24 reported that the trypsin±soya bean TI complex retained its immunological reactivity even when it reached the lower parts of the intestine. Dietary TIs are regarded as having mainly two antinutritional effects: one is an increase in endogenous protein loss due to stimulated pancreatic enzyme secretion, and the other is low availability of sulphurcontaining amino acids that are included in TIs in relatively high proportions.…”
Section: Resultsmentioning
confidence: 81%
“…8 Intestinal trypsins in the middle and lower segments were more severely suppressed when winged bean TI was fed, suggesting higher survival of the trypsin±TI complex in the intestine. Although this study determined only functional activities but not resistance to intestinal proteolysis, Iwami et al 20 and Hajos et al 24 reported that the trypsin±soya bean TI complex retained its immunological reactivity even when it reached the lower parts of the intestine. Dietary TIs are regarded as having mainly two antinutritional effects: one is an increase in endogenous protein loss due to stimulated pancreatic enzyme secretion, and the other is low availability of sulphurcontaining amino acids that are included in TIs in relatively high proportions.…”
Section: Resultsmentioning
confidence: 81%
“…In vivo studies have demonstrated the presence of active BBI in the small intestine. Hajós et al [39] reported the survival (~ 5 % of total ingested) of soybean BBI in an immunological reactive form in the small intestine of rats; unfortunately, the inhibitory activities of BBI were not evaluated in these experiments. More recently, it has been demonstrated that BBI from chickpea seeds can resist both acidic conditions and the action of digestive enzymes, and transit through the stomach and small intestine of pigs, generally held as a suitable model for human digestive physiology [40].…”
Section: Bioavailability and Metabolism Of Bbimentioning
confidence: 97%
“…The antibody was developed according to Harboe & Inglid (1973) as published before (Hajós et al, 1995). Briefly, two out-bred Hungarian Vadas rabbits weighing 2-2.5 kg were used for the immunisation with highly purified Mal d 1 or Mal d 2 antigens.…”
Section: Development Of Polyclonal Antibodies Specific To Natural Malmentioning
confidence: 99%